Experience in aneuploidies screening between 11-13+6 weeks with the Fetal Medicine Foundation algorithm - Olórtegui, Roberto Albinagorta (2013)
Objectives: To determine our experience in applying the Fetal Medicine Foundation (FMF) algorithm for first trimester aneuploidy screening in an unselected population. Design: Descriptive, retrospective, cross-sectional study. Setting: Fetal Medicine Service, Clinica Santa Isabel, Lima, Peru. Participants: Pregnant women and their fetuses. Interventions: Between March 1 and September 24 2012, nuchal translucency (NT) was measured by transabdominal ultrasound in 324 women with 11-13+6 weeks’ pregnancies and crown-rump length (CRL) between 45.0-84.0 mm. Main outcome measures: Factibility of FMF algorithm in 11-13+6 weeks screening. Results: NT curve in relation to CRLs was consistent with the quadratic equation described by FMF, and measurements followed a normal distribution with median deviation 0.2 mm lower than expected. The percentage of values above the median was 43.3%. A TN >95th percentile was observed in 4.6% of cases and TN ≥3.5 mm in 1.2%. A risk value above the 1:100 cut-off was found in 10 cases for T21 and in one case for T13. Cytogenetic study was performed in 3 patients; results were one normal female karyotype, one trisomy 18 and one extra-estructural trisomy (47XY+mar). Conclusions: Results agree with literature reports and show feasibility of FMF algorithm application in 11-13+6 weeks screening in a clinical practice setting in our country. Keywords: Ultrasound screening, aneuploidy, first trimester, nuchal translucency.